The Father’s Absence as Narrative Condition: A Genettean Reading of Intermezzo - Umama Bint e Azhar (ACADEMIA International Journal for Social Sciences, 2025)
This article explores the formal representation of grief and emotional dispassion in Sally Rooney’s Intermezzo (2024) using Gérard Genette’s theory of narrative discourse. Previous work explored Rooney’s engagement in sociocultural realism, intimacy and millennial affect; temporality focalization and voice have mediated her representations of loss with less attention. Reconceptualizing Intermezzo as a narrative through the five categories that shape Narratology (order, duration, frequency, mood, voice) allows us to show how silences, ellipses, analepses and iterative memory not only thematize absence but also represent it in structural terms. Intermezzo is anchored within current narratological discourse on fragmented narratives that represent inner emotional states. Elaborating upon Rooney’s reimagining of form as a textualization of private mourning offers a methodological bridge to approaching affect theory and structural narratology, while advancing important refinements to post-realist narrative strategies in the twenty-first century.